(untitled) (Journal of Philosophy Culture and Political Science, 2025)
In this article, the authors explore the complex relationship between language, nationalism and national unity. The authors draw attention to the socio-cultural nature of language, its integrative potential and impact on national identity. The authors systematize existing theoretical and methodological approaches, offering a new perspective on the dynamics of language and its role in strengthening national unity. The authors substantiate the role of language in shaping national identity, inclusiveness and argue that has an impact on mitigating social discord. Emphasizing effective language governance and institutional support, the authors draw attention to policies that promote social cohesion and stability, which allow for a broader understanding of the complex relationship between language and nationalism, as well as influence the strengthening of common values, the overcoming of barriers and promotion of inclusiveness, which ultimately helps to create a more stable and harmonious social environment. The scientific and practical significance of this work is that it can help specialists in this field understand the complexity of the role of language in social stability. Key words: language, national unity, nationalism, postcolonial theory, ambivalence, hybridity, mimicry.